Studies on Molecular Interactions of Some Electrolytes in Water by Volumetric and Viscometric Measurments at T= (303.15 to 323.15 K) - Kabiraz, D. C.; Biswas, T. K.; Islam, M. N.; Huque, M. E. (Journal of Scientific Research, 2011)
The viscosities and densities of potassium chloride, potassium nitrate, magnesium chloride, and magnesium nitrate have been measured at 303.15, 308.15, 313.15, 318.15 and 323.15 K in aqueous solution. The viscosity data were analyzed by using Jones–Dole equation. The values of apparent molar volume, limiting apparent molar volume have been evaluated from the density data. The results were interpreted in the light of ion–ion and ion–solvent interactions and of structural effects of the solutes in solution. Keywords: Density; Apparent molar volume; Viscosity; Jones–Dole equation. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:10.3329/jsr.v2i2.6288 J. Sci. Res. 3 (2), 437-444 (2011)